2005
DOI: 10.1002/gps.1318
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving burden and psychiatric morbidity in spouses of persons with mild cognitive impairment

Abstract: SUMMARYBackground-While the deleterious psychosocial and mental health effects of dementia caregiving are firmly established, very little is known about the burdens or psychiatric outcomes of providing care to a spouse with less severe cognitive impairment, such as mild cognitive impairment (MCI). We characterized the nature and level of caregiver burden and psychiatric morbidity in spouses of persons diagnosed with MCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
130
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(142 citation statements)
references
References 52 publications
10
130
0
2
Order By: Relevance
“…A significant association between high burden scores and psychiatric morbidity among the caregivers of schizophrenia patients is in agreement with previous findings (22,23). The association between burden and psychiatric morbidity is not surprising because of shared similarity in concept.…”
Section: Discussionsupporting
confidence: 92%
“…A significant association between high burden scores and psychiatric morbidity among the caregivers of schizophrenia patients is in agreement with previous findings (22,23). The association between burden and psychiatric morbidity is not surprising because of shared similarity in concept.…”
Section: Discussionsupporting
confidence: 92%
“…Prior work-replicated in the present study-has found that the burden of caregivers of Alzheimer's disease patients (García-Alberca et al, 2012) and individuals with mild cognitive impairment (Garand et al, 2005) is related to caregiver mental health. This suggests that the relationship between mental health and burden is fairly robust, even across mild and more severe forms of dementia caregiving.…”
Section: Discussionsupporting
confidence: 53%
“…Although level of impairment of the patients in the present study was relatively low, it can be assumed that the family members and friends performed a caregiving function (Garand et al, 2005). Written informed consent was obtained from all participants and caregivers prior to inclusion.…”
Section: Participantsmentioning
confidence: 99%